AB1013 Systemic Sclerosis and Myositis Extractable Nuclear Antigen (ENA) Analysis: Profile of A Cohort of Subjects with Isolated Raynaud's Phenomenon. (10th June 2014) - Gualtierotti, R.; Ingegnoli, F.; Schioppo, T.; Lubatti, C.; Zeni, S.; Mastaglio, C.; Galbiati, V.; Grossi, C.; Borghi, M.O.; Castelnovo, L.; Meroni, P.L.
Abstract : Background: Raynaud's phenomenon (RP) may predate an overt Connective Tissue Disease (CTD) of the "Scleroderma spectrum" such as Systemic sclerosis (SSc). The predictive role of auto-antibodies (auto-Abs) such as ANA for the development of a CTD in patients with isolated RP (i.e. with no other signs or symptoms of CTD) is well known, whereas data regarding the prevalence of anti-ENA in such patients are lacking. Objectives: Our aim was to evaluate the profile of anti-ENA in patients with isolated RP. Methods: Sera were analyzed for anti-ENA by EUROLINE "Scleroderma profile" (antigens: Scl70, CENP A, CENP B, RP11, RP155, fibrillarin (Fib), NOR90, Th/To, PM-Scl100, PM-Scl75, Ku, PDGFR, Ro-52) and "Myosites profile" (antigens: Mi-2, Ku, PM-Scl100, PM-Scl75, Jo-1, SRP, PL-7, PL-12, EJ, OJ, Ro-52) [EUROIMMUN AG Leuback, Germany]. Results: A total of 115 adults (105 females and 10 males) with isolated RP were enrolled in two Italian Rheumatology Centers (G. Pini Institute, Milan and Moriggia-Pelascini Hospital, Gravedona) from March 2011 to September 2013. Forty-four of 115 (38.0%) subjects were positive for at least one anti-ENA; 71 out of 110 (61.7%) were negative both for Scleroderma and Myosites profiles (see table 1 and 2). Conclusions: Up to 38% of RP subjects were positive for at least one anti-ENA. The detection of anti-ENA since the first Rheumatologic evaluation may aid the specialist in achieving an earlier diagnosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5955